A critical discourse analysis (CDA) of a political speech of Mr. Christian Tadele speech in the parliament - Yitbarek Mekt; Animut Getahun; Tarik Meseret (PT. MAWAMEDIA JAYAMUSTA BUANASIHA, 2024)
This paper presents a Critical Discourse Analysis (CDA) of a political speech delivered by Mr. Christian Tadele in the Ethiopian parliament. The study aims to uncover hidden ideologies, future agendas, and linguistic components in Mr. Tadele's speech through the examination of strategies such as politeness and inclusive language, as well as the analysis of frequently used words like